EXPERIENCE OF TRAINING OF EXPERTSIN THE FIELD OF EDUCATION IN THE BALTIC COUNTRIES - Tryhub, Ilona (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the experience of training of experts in the field of education in the Baltic countries (Lithuania, Latvia and Estonia). It identified the following common features of professional training of experts in the field of education: focus on quality assurance; implementation of vocational training as part of Continuing Education; seminars and conferences as the basic forms of training; lack of training of experts in the field of education in universities; election of candidates for experts in the field of education from experienced teachers with the experience and good practice; compliance with official Code of Ethics of professional experts in the field of education; International cooperation in quality assurance. Specific trends in training of experts in the field of education are observed in Lithuaniaand Estonia. We can enroll the following special trends in training of experts in the field of education in the Baltic countries as: • mandatory briefing – introductory workshop, where candidates for experts in the field of education are informed about the current progress of cases, the parties’ positions, previously unknown details, get answers to key questions (experience of Lithuania); • for development of necessary knowledge and skills in carrying out the expertise, candidates who fit the role of expertsin the field of education, the agency offers annual training (experience of Estonia).